Outdoor cultivation of a novel isolate of the microalgae Scenedesmus sp. and the evaluation of its potential as a novel protein crop. Issue 2 (15th September 2021) - Olsen, Malene Fog Lihme; Pedersen, Jakob Skov; Thomsen, Sune Tjalfe; Martens, Helle Jakobe; Petersen, Annette; Jensen, Poul Erik
Abstract: A Danish strain of the green microalgae Scenedesmus sp. was isolated, identified and characterized with respect to productivity under outdoor cultivation conditions at northern latitudes. The algae were cultivated outdoors in Denmark in closed tubular photobioreactors using only sunlight, simple inorganic nutrients and under ambient temperatures. The biomass composition was evaluated in terms of protein content and quality. The average volumetric and areal biomass productivity obtained for the Scenedesmus sp. isolate during outdoor cultivation was 0.083 g dry matter L −1 and 6.40 g dm m −2  day −1, respectively. Thus, productivities are comparable to data reported in the literature under similar conditions. A strain‐specific nitrogen to protein conversion factor of 5.5 was determined for the Scenedesmus sp. strain enabling more accurate protein estimations from simple nitrogen determination methods like Kjeldahl analysis in the future. The protein content was determined to be 52.4% of dried biomass for this Scenedesmus strain. The sum of essential amino acids was 42% which is high compared to other microalgae. The results are compared and discussed in comparison to other microalgae and soybean as a common plant protein source.